UNIVERSITY STAKEHOLDERS’ ATTITUDE TOWARD UTILIZING E-TUTORING FOR DISTANCE LEARNING - Oyeronke Olufunmilola OGUNLADE; Esther JOSHUA; Olubode OLUMORIN Charles (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
This study examined University stakeholders’ (academic and technical staff) attitude toward the use of E-tutoring for distance learning in Nigeria. It specifically investigated attitude towards the use of E-tutoring based on gender, working experience and area of specialization. Questionnaire was used to collect data from 157 respondents involved. Four research questions were answered while three hypotheses were tested. Mean and percentage were used to answer the research questions and independent t-test for the hypotheses. Results indicated :stakeholders had positive attitude (mean score :3.10); no significant difference between male and female ( t-test value of df (155), t = 1.49, p > .05); no significant difference between experienced and less experienced (t-test value of df (155), t = -.84, p > .05); no significant difference between stakeholders(df (155), t = 1.69, p > .05). It was recommended that etutoring should be more incorporated into distance learning in Nigeia